Cidade clandestina, dano colateral das leis urbanísticas: a regularização de edificações e os impactos na produção e gestão das cidades - Juliana Mattos Magnani (2018)
The primary mean for urban planning practices in Brazil is through legislation. Nonetheless, legal tools severely limit the pursuit of the right to the citythe modification of the city for the collective living. Urban laws contain implicit models of ideal cities and ideal citizens, which keep the laws removed from the daily practices that modify the urban space. From this perspective, the irregular constructions are collateral damage of this process of making laws distant from the habits and the needs of the inhabitants of the city. Using the case of the city of Belo Horizonte, I studied the effect of laws that allows the formalization of illegal buildings through payment both on the production of the city space and on urban management. Further, I discuss the reach and limitations of regularization' laws and their capability of inclusion of those who have built illegally and contrasted the urban planning theories of Françoise Choay, Pierre Bourdieu, Michel Foucault, and Zygmunt Bauman with the local Brazilian context. The empirical observation included a timeline with the construction laws from Belo Horizonte and another with the regularization laws from the same city. I also used data from the construction permits and regularization and from surveys made with city hall civil servants and with architects and engineers that works with building permits and regularization. This analysis aimed the understanding of who, and how, theses regularization laws can attend, and what are its consequences on urban spaces and on political environment. I concluded that the attempt to reduce informality through permissive laws is as limited as the attempt to guarantee rights solely through inclusive laws. Neither tool acts on the causes of the clandestine constructions. For some social groups, the highest income, informality causes no significant consequences. Therefore, there is no reason for them to seek legalization. For the lowest income, informality is not limited to the means of constructing but also spreads to other domains of life such as informal ownership of the land and informal work relations, which also implies that regularization has no use for them. Finally, for urban planning, these laws do not contribute to guaranteeing the right to the city.